Early Dorset in the High Arctic: A Report from Karluk Island, N.W.T. - Helmer, James W. (ARCTIC, 1980)
During the months of July and August 1978, a programme of archaeological excavations was conducted on Karluk Island in the Crozier Strait region of the Canadian High Arctic. The purpose of this project was to continue the examination, begun in 1977, of a number of early Dorset sites . The objectives were to recover a sufficient sample of artifacts to legitimately conduct inter-regional comparisons, and to obtain ancillary data pertaining to structure types, subsistence patterns, seasonality and date of occupation. In the . paper, the data obtained during the 1978 season are summarized and the significance of this material to High Arctic prehistory is briefly assessed.